Students' Geographic Literacy Abilities - Ramadhani, Amalia; Ruhimat, Mamat; Sugito, Nanin Trianawati (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
One of the abilities that students must master in the 21st century is literacy skills, one of which is geographic literacy. Based on previous research, students' geographic literacy, in general, still needs to improve. This research aims to determine and analyze the geographic literacy abilities of State High School (SMA) students in Jambi City. This research uses a survey method. The data processing results show that the geographic literacy skills of 190 State High School students in Jambi City are in the medium category with a percentage of 51% or 97 students. This means the students can understand the essence of interaction, interconnection, and the contextual implications of spatial interaction phenomena in life. Daily for some instances only. Meanwhile, the number of students in the high geographical literacy category is 43 or 23%, so it can be interpreted that students can understand the essence of interaction, interconnection and the implications of spatial interaction phenomena contextually in everyday life. Geographic literacy skills in the low category are 50 students or 26%, which means that students still need to understand the essence of interaction, interconnection and the implications of spatial interaction phenomena contextually in everyday life.